2001
DOI: 10.1128/jb.183.9.2888-2896.2001
|View full text |Cite
|
Sign up to set email alerts
|

Bap, a Staphylococcus aureus Surface Protein Involved in Biofilm Formation

Abstract: Identification of new genes involved in biofilm formation is needed to understand the molecular basis of strain variation and the pathogenic mechanisms implicated in chronic staphylococcal infections. A biofilmproducing Staphylococcus aureus isolate was used to generate biofilm-negative transposon (Tn917) insertion mutants. Two mutants were found with a significant decrease in attachment to inert surfaces (early adherence), intercellular adhesion, and biofilm formation. The transposon was inserted at the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
646
5
26

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 755 publications
(724 citation statements)
references
References 50 publications
14
646
5
26
Order By: Relevance
“…By using the 3D-PSSM-fold recognition server (Kelley et al, 2000), we initially found 14 enterococcal CWA proteins with predicted Ig-like folds among the panel of 29 putative CWA proteins identified by us. Four of these are highly conserved aggregation substance (Galli et al, 1990(Galli et al, , 1992 homologues (77 % overall identity in multiple alignment) and one shows significant similarity (31 % identity over 1457 aa) to the biofilm-associated protein (Bap) of S. aureus (Cucarella et al, 2001). As we were focusing on novel and uncharacterized CWA proteins with MSCRAMM-like structural features, we chose the remaining nine proteins (EF0089, EF1091, EF1092, EF1093, EF1099, EF1269, EF1824, EF2224 and EF3023; TIGR annotation locus names have been used throughout this study) for further investigation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By using the 3D-PSSM-fold recognition server (Kelley et al, 2000), we initially found 14 enterococcal CWA proteins with predicted Ig-like folds among the panel of 29 putative CWA proteins identified by us. Four of these are highly conserved aggregation substance (Galli et al, 1990(Galli et al, , 1992 homologues (77 % overall identity in multiple alignment) and one shows significant similarity (31 % identity over 1457 aa) to the biofilm-associated protein (Bap) of S. aureus (Cucarella et al, 2001). As we were focusing on novel and uncharacterized CWA proteins with MSCRAMM-like structural features, we chose the remaining nine proteins (EF0089, EF1091, EF1092, EF1093, EF1099, EF1269, EF1824, EF2224 and EF3023; TIGR annotation locus names have been used throughout this study) for further investigation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One candidate for biofilm formation is a large 1,987-residue protein (LSA0534) composed of 15 perfectly conserved 100-amino-acid repeats and of an LPXTG motif (PF00746) involved in covalent anchoring to the cell wall. It demonstrates 37% similarity to Biofilm Associated Protein (BAP) found in bovine Staphylococcus aureus strains 33 . We further identified four paralogous proteins predicted to mediate autoaggregation and adherence to collagen 34 .…”
Section: Heme and Iron Requirementmentioning
confidence: 88%
“…In general, pathogenicity and persistence of these infections are associated with biofilm forming capability. Many surface proteins are reported to be involved in biofilm formation such as SasG [14], FnBPA and FnBPB [15], and the biofilm-associated protein Bap [3]. The Bap protein is encoded by a 6831 bp long bap gene.…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors is the expression of Biofilm-associated protein which confers the capacity to form biofilm. It also plays a crucial role in bacterial infection process even in the absence of ica operon, which is responsible for polysaccharide intercellular adhesion (PIA)/poly-β-1,6-N-acetylglucosamine (PNAG) synthesis [3]. Bap was the first protein among the family of large surface proteins that is reported to be involved in initial attachment to surfaces and assist in cell-cell interactions [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation